(untitled) (Annals of Medical Research, 2022)
Aim: This study aimed to examine integrated anxiety and stress states and quality of life of healthcare workers during the COVID-19 process and the relationship between them. Materials and Methods: The population of this descriptive, cross-sectional, and correlational study consisted of all healthcare workers working during the COVID-19 process in Turkey. The research sample consisted of 305 healthcare workers who could be reached online between 12 June and 25 August 2020. In the study, a “Personal Information Form”, the “Integrated Anxiety-Stress Scale (IASS)”, and the “Professional Quality of Life Scale (ProQOL)” were used. Results: Of the healthcare workers, 85.2% were female, 72.5% were married, and 81.6% were nurses. 59.7% of them were assigned to COVID-19 units during the pandemic process. The mean total IASS score of the healthcare workers was 56.34±28.70 and the mean IASS index score was 26.17±8.30. The mean scores on the subscales of ProQOL were 32.64±10.17 for professional satisfaction, 15.70±9.32 for empathy fatigue, and 19.88±7.22 for burnout. A strong significant relationship was found between the integrated anxiety/stress scale and the subscales of the professional quality of life scale (p<0.01). According to the regression analysis, burnout and empathy fatigue, which are the subscales of the professional quality of life scale, affected the integrated anxiety stress scale score (p<0.01). Conclusion: This study, which was carried out in the middle and advanced periods of the outbreak, showed that the integrated stress-anxiety levels of healthcare workers were moderate and high. Increased integrated anxiety/stress increases burnout and empathy fatigue whereas it reduces professional satisfaction and predicts burnout and empathy fatigue. Therefore, in order to reduce the burnout level and empathy fatigue of healthcare professionals, interventions should be made to control/reduce their anxiety and stress levels.